Effect of parameters on retention behavior of ovalbumin and immunoglobulin E in asymmetrical flow field‐flow fractionation. Issue 11 (1st September 2022) - Liang, Qihui; Li, Yang; Zou, Yue; Shu, Lin; Han, Nanyin; Yang, Yi
Abstract: Asymmetrical flow field‐flow fractionation is a rising useful technique to separate and characterize macromolecules. Elution behaviors of allergen protein ovalbumin and immunoglobulin E were studied here. Effects of flow rates, kinds of carrier solutions, and injection amounts were investigated in the desire to experiment and verify the effect of every factor and to validate asymmetrical flow field‐flow fractionation theory. Results suggested that cross‐flow is the most important factor among all the factors that have been studied. Too‐low focus flow (0.5 ml/min) and outflow (0.4 ml/min) are harmful for protein separation and characterization. Smaller size ovalbumin (with a monomer is 11.4 nm) is more prone to be influenced compared with the bigger analyte immunoglobulin E (with a monomer diameter is 32.1 nm) by flow rates. The adopted types of carrier fluids did not change the retention behavior of the two proteins. Still, protein aggregation and membrane adsorption should be paid more attention to under different carrier fluids.